2009
DOI: 10.1590/s0100-204x2009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica do pH da água das chuvas em Passo Fundo, RS

Abstract: Resumo -O objetivo deste trabalho foi avaliar a dinâmica do pH da água das chuvas em Passo Fundo, RS, de 1992 a 2007. A água foi coletada em recipiente de PVC (diâmetro de 10 cm) acoplado a um pluviômetro, e as amostras foram armazenadas em congelador para posterior determinação do pH. A dinâmica do pH da água foi avaliada por meio das médias mensais e anuais do pH, da probabilidade empírica da distribuição dos valores anuais de pH por estação do ano e da frequência relativa acumulada do pH. A água das chuvas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
3
0
4
Order By: Relevance
“…In a general way, the period with most rain (the Summer) had the lowest averages of pH. The study carried out by Cunha et al 18 showed that in Summer and Spring, the pH was slightly lower than in the Fall and Winter, which reveals the dynamics of the pH of rainfall. Solar radiation gives rise to reactions of gases with the rain and thus forms acids that can reduce the pH, 19 which explains why Summer is the season with the lowest averages of pH.…”
Section: Hydrogenionic Potential (Ph)mentioning
confidence: 95%
“…In a general way, the period with most rain (the Summer) had the lowest averages of pH. The study carried out by Cunha et al 18 showed that in Summer and Spring, the pH was slightly lower than in the Fall and Winter, which reveals the dynamics of the pH of rainfall. Solar radiation gives rise to reactions of gases with the rain and thus forms acids that can reduce the pH, 19 which explains why Summer is the season with the lowest averages of pH.…”
Section: Hydrogenionic Potential (Ph)mentioning
confidence: 95%
“…Valores de pH igual ou acima de 5,6 são considerados normais devido à absorção de CO2 e concentração natural de H2CO3 na água presente na atmosfera (GALLOWAY et al, 1982;BAIRD, 2002). Cunha et al (2009) A variação do pH no período analisado nesta pesquisa pode ter sido influenciada devido à quantidade de chuva precipitada nas datas de amostragem.…”
Section: Mpv =unclassified
“…Comparing the locations analyzed in Congonhas, the point CA 03, which is located near the historic center where the Aleijadinho's sculptures are located, was the one with the lowest pH values. Cunha et al (2009) considered that the pH of rainwater equal to or greater than 5.6 as normal, between 5 to 5.6 slightly acidic and less than 5 is acidic. Therefore, the only Turbidity (uT)…”
Section: Apparent Color (Uh)mentioning
confidence: 99%